Pengembangan Media Pembelajaran Boardgame Matematika Kelas XII Dengan Materi Dimensi Tiga di SMA Negeri 51 Jakarta - Wahyu Seto Ramadhan; Lidia Zahra; Vania Al-Fitri Shafwan (Algoritma : Jurnal Matematika, Ilmu pengetahuan Alam, Kebumian dan Angkasa, 2024)
The development of technology in the world at this time is very influential and has an impact on education. Therefore, interactive learning media is needed with the aim of attracting the attention of students. The purpose of this research is (1) Producing learning media in the form of board games with three-dimensional material for students 12th Grade SMA Negeri 51 Jakarta. (2) Knowing the effectiveness of learning media for students 12th Grade SMA Negeri 51 Jakarta. The research method used is the model ADDIE (Analysis, Design, Development, Implementation, Evaluate). because the research method with the ADDIE model has systematic and specific steps in each stage